2012
DOI: 10.1115/1.4007934
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methods to Fully Saturate Carbon Foam With Paraffin Wax Phase Change Material for Energy Storage

Abstract: In this work, the effect of infiltration method on the saturation rate of paraffin phase change material within graphite foams is experimentally investigated. Graphite foams infiltrated with paraffin have been found to be effective for solar energy storage, but it has been found that it is difficult to completely saturate the foam with paraffin. The effectiveness of the fill will have a significant effect on the performance of the system, but the data on fill ratio are difficult to separate from confounding ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…However, due to no mechanism for displacing trapped air, this infiltration technique can result in infusions as low as 45% [18]. Some have used vacuum infiltration, in which the foam is evacuated before or during infusion.…”
Section: B Foam Sample Preparationmentioning
confidence: 98%
See 1 more Smart Citation
“…However, due to no mechanism for displacing trapped air, this infiltration technique can result in infusions as low as 45% [18]. Some have used vacuum infiltration, in which the foam is evacuated before or during infusion.…”
Section: B Foam Sample Preparationmentioning
confidence: 98%
“…The paraffin-infused samples provided a control, since this type of TES has been studied extensively [8,17,18]. The intent was to evaluate the TES performance of PG-infused samples relative to paraffin samples by subjecting them to the same conditions.…”
Section: Paraffin-infused Control Samplementioning
confidence: 99%
“…A study by Warzoha et al [19] showed that the commonly used method of submerging the foam or expanded graphite in melted PCM and letting it wick into the solid is ineffective. Repeated tests showed that at least 25% of the reported open space within the foam was left unfilled using this method.…”
Section: Use Of Carbon Based Materials For Performance Enhancementsmentioning
confidence: 99%
“…Repeated tests showed that at least 25% of the reported open space within the foam was left unfilled using this method. It was shown that for effective use of these materials the foam must be fully evacuated and then filled under vacuum conditions [19].…”
Section: Use Of Carbon Based Materials For Performance Enhancementsmentioning
confidence: 99%
“…Recent development of graphite foams with extremely high bulk thermal conductivities [21] has led to several investigations on using them for improving the thermal performance of low thermal conductivity materials [22][23][24][25][26][27][28]. Zhong et al [24] showed that the thermal diffusivity of a paraffin/graphite foam composite was 570 times higher than that of pure paraffin wax.…”
Section: Introductionmentioning
confidence: 99%